(3QSGdI aj GdYde heGgjJgs - (3GdJhbGOj GdESJGfHhdj GdYKeGfj GdMfaj, GHf ceGd HGTG, ceGd HGTG RGOg, TeS GdOjf, CMeO Hf SdjeGf Hf ceGd HGTG, (B940 (3g`s
(3ChdgG (B:s
(3bGd Cgd GdMbGFb(B: (3MbGFb GdCTjGA KGHJI hGdYde HgG eJMbb NdGaG ddShaSWGFjI hCSHGH GdYde ddNdb KdGKI GdMhGS GdSdjeI hGdNHQ GdUGOb hGdYbds
(3BNQgG (B:s
(3hjLhR GdYbGH Ydi GdUZjQI hGdYah Yf GdcHjQI EPG de jcf Yf GSJMdGd, hGdGSJMdGd caQ, hGdTaGYI KGHJI ddQSd hGdCNjGQ aj Mb Cgd GdcHGFQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 1 / 133s
(3eYLe GdeDdajf(B: 3 /148s
(3cTa GdXfhf(B: 1 / 878s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdJUha hGdBOGH GdTQYjIs